Serine ADP-Ribosylation Depends on HPF1 - Bonfiglio, J; Fontana, P; Zhang, Q; Colby, T; Gibbs-Seymour, I; Atanassov, I; Bartlett, E; Zaja, R; Ahel, I; Matic, I (Cell Press, 2017)
ADP-ribosylation (ADPr) regulates important patho-physiological processes through its attachment to different amino acids in proteins. Recently, by precision mapping on all possible amino acid residues, we identified histone serine ADPr marks in the DNA damage response. However, the biochemical basis underlying this serine modification remained unknown. Here we report that serine ADPr is strictly dependent on histone PARylation factor 1 (HPF1), a recently identified regulator of PARP-1. Quantitative proteomics revealed that serine ADPr does not occur in cells lacking HPF1. Moreover, adding HPF1 to in vitro PARP-1/PARP-2 reactions is necessary and sufficient for serine-specific ADPr of histones and PARP-1 itself. Three endogenous serine ADPr sites are located on the PARP-1 automodification domain. Further identification of serine ADPr on HMG proteins and hundreds of other targets indicates that serine ADPr is a widespread modification. We propose that O-linked protein ADPr is the key signal in PARP-1/PARP-2-dependent processes that govern genome stability.